Efforts to Recover State Financial Losses Through Criminal Cases Case Study Against Corruption - Andri, Fira Saputri Yanuar; Holish, Amarru Muftie; Wicaksono, Aditya (Law Research Review Quarterly, 2019)
State Assets are objects of the criminal acts of corruption which are certainly very detrimental to the State if viewed from the perspective of the victim . However, the victims of embezzlement of state funds are not only the State but also the people . The real consequence of this action is the reduced wealth of the State which should be used as a collision of assets owned by the State . Efforts to restore state losses based on the existing criminal procedural law procedure seems unable to maximize the return of stolen State assets . Supposedly, the country here holds legal protection because here one of the victims of the stolen state assets is certainly the country itself. As one of the crimes based on counts it seems that there needs to be an alternative solution in returning the lost state assets .